Gold-catalysed nitroalkyne cycloisomerization - synthetic utility - Dhote, Pawan S.; Halnor, Swapnil V.; Ramana, Chepuri V. (Chemical Record, 2021)
The gold-catalysed intramolecular redox cyclization of o-alkynylnitrobenzens documented by Professors Naoki Asao and Yoshinori Yamamoto is an important discovery that has opened two complementary research domains. Advancing this cyclization with other metals as well as developing new methods around the products that result from this reaction is one aspect that has seen growing interest. On the other hand, the idea of generating alpha-oxo gold carbenes via oxygen transfer to alkynes has established another important aspect in gold-catalysis. In this account, we will be dealing with the first aspect, which revolves around the internal redox cyclization of nitroalkynes (trivially called as nitroalkyne cycloisomerization), focusing mainly on the gold-complexes and the synthetic methods developed around it from our group and from other groups, and also providing the details of similar transformations documented with other metals so that the complementary reactivity/diversity of these transformations could be appreciated.
Keywords: alpha-Oxo Gold Carbene; Anthranil; Gold-catalysis; Internal Redox Cyclization; Isatogen

Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX

Attempted synthesis of the central 2,2-disubstituted pseudoindoxyl core of Austamide via a [Au]-catalyzed nitroalkyne cycloisomerization and intramolecular [3+2]-cycloaddition - Halnor, Swapnil V.; Ramana, Chepuri V. (Tetrahedron, 2024)
Herein, we describe an Au-catalyzed cycloisomerization process of a nitroalkyne that was projected to construct the central 2,2-disubstituted pseudoindoxyl core of the natural product Austamide. Our intended strategy for forging the pseudoindoxyl core is based on the nitroalkyne cycloisomerization followed by a subsequent intramolecular [3 + 2] cycloaddition. However, the [3 + 2] cycloaddition occurred in an undesired manner, ultimately leading to a complex hexacyclic scaffold.
Keywords: Austamide; Gold catalysis; Intramolecular [3+2] cycloaddition; Nitroalkyne cycloisomerization

Synthesis of tetracyclic benzoxazolo-indol-3-ones from isatogens and arynes through a [3+2]-cycloaddition and skeletal reorganization - Halnor, Swapnil V.; Singh, Maneesha; Dhote, Pawan S.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2024)
The construction of an unprecedented tetracyclic benzoxazolo-indol-3-one scaffold has been executed through the [3 + 2]-cycloaddition of isatogens with arynes. The initially formed benzisoxazolo-indol-3-one intermediate undergoes a skeletal reorganization through a 1,3-sigmatropic shift/retro-Mannich reaction with the net formation of one C-N and two C-O bonds. The Lewis acid-catalyzed allylation of some of the resulting benzoxazolo-indol-3-ones resulted in oxazepino-indolones with promising photophysical properties.